Biomass production, water use efficiency and nutritional value parameters of sorghum (Sorghum bicolor L.) genotypes as affected by seed hydro-priming and transplanting - Mirahki, Isaac; Ardakani, Mohammad Reza; Golzardi, Farid; Paknejad, Farzad; Mahrokh, Ali (Acta Biologica Szegediensis, 2022)
To investigate hydropriming and transplanting effect on biomass and nutritional content of forage sorghum, a two-year field experiment was conducted in the semiarid condition of Iran. Experimental factor consisted of planting dates (July-1st, July-11th, July-23rd, August-1st) in the main plot and the factorial combination of planting methods (direct planting, hydropriming, transplanting) with cultivars (Speedfeed and Pegah) in the subplot. Planting date postponement from 1st of July to 10th of July, 23rd of July, and 1st of August, respectively, caused 16.1, 32.5 and 47.2% reduction in dry matter yield (DMY) and 7.4, 20.2, and 35.1% reduction in water use efficiency of DMY production (WUEDMY). Hydropriming and transplanting produced 23.6 and 22.4% more DMY, 24.5 and 21.8% more WUEDMY, 24 and 16.3% more crude protein yield, 22.7 and 20.9% more digestible dry matter (DDM) yield, and 22.2 and 20.1% more metabolic energy (ME) yield, compared to the direct planting. Hydropriming compared to direct planting caused 29% increase in plant growth rate and utilized growing season more productively than transplanting for DMY production. Conclusively, hydropriming and transplanting compensated for delay in planting through enhancing and accelerating germination and plant development but, applying hydropriming on Speedfeed and planting in July-1st caused the highest DMY, WUEDMY and the yield of nutritive parameters.